2017
DOI: 10.1098/rsbl.2016.0863
|View full text |Cite
|
Sign up to set email alerts
|

Climate predicts which sex acts as helpers among cooperatively breeding bird species

Abstract: Among avian cooperative breeders, help in raising offspring is usually provided by males or by both sexes. Sex bias in helping should evolve in response to sex-specific ecological constraints on independent reproduction, with mate shortage for males and breeding vacancy shortage for each sex. Given that male-biased adult sex ratios are prevalent among birds, we predict that maleonly helping mainly occurs in temperate species where fast population turnovers deriving from low adult annual survival allow all adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…At present, efforts to evaluate this are hampered by the fact that broad patterns of sex-biased dispersal tend to be evaluated with respect to dispersal probability and/or dispersal distance (Clarke et al, 1997;Mabry et al, 2013;Trochet et al, 2016;Li and Kokko, 2019). We have shown that timing can also be kin-selected, but the comparative studies available to evaluate this factor are rather focused on delayed dispersal in cooperative breeding, where philopatry also offers individuals the opportunity to become helpers (Zhang et al, 2017). These additional kin-selected opportunities are interesting in their own right (Johnstone and Cant, 2008), but our model shows that interesting phenomena can arise even if the only form of helping and harming is the choice between dispersal and continuing to deplete local resources, with no other layers of social complexity.…”
Section: Discussionmentioning
confidence: 99%
“…At present, efforts to evaluate this are hampered by the fact that broad patterns of sex-biased dispersal tend to be evaluated with respect to dispersal probability and/or dispersal distance (Clarke et al, 1997;Mabry et al, 2013;Trochet et al, 2016;Li and Kokko, 2019). We have shown that timing can also be kin-selected, but the comparative studies available to evaluate this factor are rather focused on delayed dispersal in cooperative breeding, where philopatry also offers individuals the opportunity to become helpers (Zhang et al, 2017). These additional kin-selected opportunities are interesting in their own right (Johnstone and Cant, 2008), but our model shows that interesting phenomena can arise even if the only form of helping and harming is the choice between dispersal and continuing to deplete local resources, with no other layers of social complexity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparative analysis showed that mate limitation is more likely to operate in temperate regions and leads to male-only helping, whereas breeding-vacancy limitation tends to apply to subtropical and tropical regions and promotes helping by both sexes (Zhang et al 2017). The former case should be true for the Ground Tits where the two conditions required for the mate constraint hypothesis are met.…”
Section: Discussionmentioning
confidence: 99%
“…This was also the case for territory quality, which was a poor predictor of a helper's presence (2). Compared with the only previous estimate for the heritability of helping behavior in the wild (8), ours (2) was based on a more accurate pedigree, and the result (0.47) represents a relatively high value that indicates the role of genes (9), although helping behavior can also be promoted by environments (10). We encourage future studies to take into account more factors such as maternal and dominant effects to obtain further details about the genetic component of this important social behavior.…”
mentioning
confidence: 68%